Implementation Of Global Positioning System As A Location Monitoring Media For Final Project Guidelines On Android-Based Applications - Riki Ahmad Fauji; Alam Rahmatulloh (Jurusan Teknologi Informasi Universitas Semarang, 2019)
Final Project is the written result of a series of activities, starting from data collection, implementation of a study to the preparation of reports. In working on a Final Project a student is required to conduct guidance with a supervisor who has been determined by the institution. There are difficulties in arranging the guidance schedule for lecturers because there are teaching schedules, as well as out-of-town service activities. In this study, mobile applications will be developed that can be used by students and lecturers in communication and for students to find out the whereabouts of lecturers by utilizing GPS facilities. The research method used is the Design and Creation method which has 5 stages, namely awareness, suggestion, development, evaluation, and conclusion. In the development stage using the Extreme Progmingming system development method. Based on the results of testing, the Online Final Assignment Student Assignment application that was built was able to display the location of the existence of the supervisor, guidance schedule and chat services connected with the WhatsApp application as a means to communicate between Lecturers and Students.